3D Photogrammetry Reveals Dynamics of Stony Coral Tissue Loss Disease (SCTLD) Lesion Progression Across a Thermal Stress Event - Meiling, Sonora; Muller, Erinn M.; Smith, Tyler B.; Brandt, Marilyn E. (Frontiers in Marine Science, 2020)
Stony coral tissue loss disease (SCTLD) was first observed in the United States Virgin Islands in January 2019 on a reef at Flat Cay off the island of St. Thomas. A year after its emergence, the disease had spread to several reefs around St. Thomas causing significant declines in overall coral cover. Rates of tissue loss are an important metric in the study of coral disease ecology, as they can inform many aspects of etiology such as disease susceptibility and resistance among species, and provide critical parameters for modeling the effects of disease among heterogenous reef communities. The present study quantified tissue loss rates attributed to SCTLD among six abundant reef building species (Colpophyllia natans, Montastraea cavernosa, Diploria labyrinthiformis, Pseudodiploria strigosa, Orbicella annularis, and Porites astreoides). Field-based 3D models of diseased corals, taken approximately weekly, indicated that the absolute rates of tissue loss from SCTLD slowed through time, corresponding with the accumulation of thermal stress that led to mass bleaching. Absolute tissue loss rates were comparable among species prior to the bleaching event but diverged during and remained different after the bleaching event. Proportional tissue loss rates did not vary among species or through time, but there was considerable variability among M. cavernosa colonies. SCTLD poses a significant threat to reefs across the Caribbean due to its persistence through time, wide range of susceptible coral species, and unprecedented tissue loss rates. Intervention and management efforts should be increased during and immediately following thermal stress events in order maximize resource distribution when disease prevalence is decreased.